Capabilities and complexity of computations with integer division - Lürwer-Brüggemeier, Katharina; Meyer auf der Heide, Friedhelm (Lecture Notes in Computer Science)

Periodic Sorting on Two-Dimensional Meshes - Kutylowski, Miroslaw; Wanka, Rolf (Parallel Processing Letters 2)
We consider the following periodic sorting procedure on two-dimensional meshes of processors: Initially, each node contains one number. We proceed in rounds each round consisting of sorting the columns of the grid, and, in the second phase, of sorting the rows according to the snake-like ordering. We exactly characterize the number of rounds necessary to sort on an l × m-grid in the worst case, where l is the number of the rows and m the number of the columns. An upper bound of ⌈ log l⌉ + 1was known before. This bound is tight for the case that m is not a power of 2. Surprisingly, it turns out that far fewer rounds are necessary if m is a power of 2 (and m ≪ l) in this case, exactly min { log m + 1, ⌈ log l⌉ + 1} rounds are needed in the worst case.

High performance universal hashing, with applications to shared memory simulations - Dietzfelbinger, Martin; Meyer auf der Heide, Friedhelm (Data structures and efficient algorithms)

Hashing strategies for simulating shared memory on distributed memory machines - Meyer auf der Heide, Friedhelm (Lecture Notes in Computer Science)

On the performance of networks with multiple busses - Meyer auf der Heide, Friedhelm; Pham, Hieu Thien (STACS 92)

Efficient PRAM simulation on a distributed memory machine - Karp, Richard M.; Luby, Michael; Meyer auf der Heide, Friedhelm (Proceedings of the twenty-fourth annual ACM symposium on Theory of computing - STOC '92)

Dynamic Hashing in Real Time - Dietzfelbinger, Martin; Meyer auf der Heide, Friedhelm (TEUBNER-TEXTE zur Informatik)

Approximation of convex polygons - Alt, Helmut; Blömer, Johannes; Wagener, Hubert (Automata, Languages and Programming)

A new universal class of hash functions and dynamic hashing in real time - Dietzfelbinger, Martin; Meyer auf der Heide, Friedhelm (Automata, Languages and Programming)

Dynamic hashing strategies - Meyer auf der Heide, Friedhelm (Lecture Notes in Computer Science)

On the complexity of genuinely polynomial computation - Karpinski, Marek; Meyer auf der Heide, Friedhelm (Lecture Notes in Computer Science)

How to distribute a dictionary in a complete network - Dietzfelbinger, M.; Meyer auf der Heide, Friedhelm (Proceedings of the twenty-second annual ACM symposium on Theory of computing - STOC '90)

Not all keys can be hashed in constant time - Gil, J.; Meyer auf der Heide, Friedhelm; Wigderson, A. (Proceedings of the twenty-second annual ACM symposium on Theory of computing - STOC '90)

Das Heinz Nixdorf-Institut der Universität-GH Paderborn - Meyer auf der Heide, Friedhelm (Informatik Spektrum)

On computations with integer division - Just, Bettina; Meyer auf der Heide, Friedhelm; Wigderson, Avi (RAIRO - Theoretical Informatics and Applications)

An optimal parallel dictionary - Dietzfelbinger, M.; Meyer auf der Heide, Friedhelm (Proceedings of the first annual ACM symposium on Parallel algorithms and architectures - SPAA '89)

On genuinely time bounded computations - Meyer auf der Heide, Friedhelm (STACS 89)

Time-optimal simulations of networks by universal parallel computers - Meyer auf der Heide, Friedhelm; Wanka, Rolf (STACS 89)

Computing minimum spanning forests on 1- and 2-dimensional processor arrays - Meyer auf der Heide, Friedhelm (STACS 89)

On the limits of computations with the floor function - Babai, László; Just, Bettina; Meyer auf der Heide, Friedhelm (Information and Computation)